2005
DOI: 10.1158/1078-0432.ccr-04-1937
|View full text |Cite
|
Sign up to set email alerts
|

Phase I and Pharmacokinetic Study of the Dolastatin 10 Analogue TZT-1027, Given on Days 1 and 8 of a 3-Week Cycle in Patients with Advanced Solid Tumors

Abstract: Purpose: TZT-1027 {N2-(N,N-dimethyl-l-valyl)-N-[(1S,2R)-2-methoxy-4-[(2S)-2-[(1R,2R)-1-methoxy-2-methyl-3-oxo-3-[(2-phenylethyl)]amino]propyl]-1-pyrrolidinyl]-1-[(S)-1-methylpropyl]-4-oxobutyl]-N-methyl-l-valinamide} is a cytotoxic dolastatin 10 derivative inhibiting microtubule assembly through the binding to tubulins. The objectives of this phase I study was to assess the dose-limiting toxicities (DLT), to determine the maximum tolerated dose, and to study the pharmacokinetics of TZT-1027 when given i.v. ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(38 citation statements)
references
References 21 publications
0
38
0
Order By: Relevance
“…Data has shown that 33% of patients treated with TZT-1027 had stable disease as defined by RECIST criteria. Another phase I trial of TZT-1027 in 17 patients treated on days 1 and 8 of a 3-week course was reported (134). A partial response within 50 weeks of treatment in a patient with metastatic liposarcoma was observed.…”
Section: C) Tubulin-targeting Agentsmentioning
confidence: 92%
“…Data has shown that 33% of patients treated with TZT-1027 had stable disease as defined by RECIST criteria. Another phase I trial of TZT-1027 in 17 patients treated on days 1 and 8 of a 3-week course was reported (134). A partial response within 50 weeks of treatment in a patient with metastatic liposarcoma was observed.…”
Section: C) Tubulin-targeting Agentsmentioning
confidence: 92%
“…Many compounds isolated from cyanobacteria such as dolastatins, curacins, and cryptophycins have shown antitumor activity (Simmons et al, 2005). Among these, dolastatin 10 and cryptiphycin 52 have entered into clinical trials for solid tumors (Jonge et al, 2005) and lung cancer, respectively (Edelman et al, 2005). Kreitlow and Sabine (1999) evaluated the antibiotic activities of hydrophilic and lipophilic extracts of 12 strains of cyanobacteria collected from fresh and brackish water.…”
Section: Introductionmentioning
confidence: 99%
“…The dose-limiting toxicities during phase 1 trials included fatigue, neutropenia, peripheral neuropathy, constipation, hyponatremia, and pain at the infusion site. 97,98 The agent was tested in sarcoma and nonsmall cell lung cancer during phase 2 development. Flavanoids 5,6-dimethylxanthenone-4acetic acid (DMXAA, AS-1404) is a flavanoid derivative that damages DNA and induces apoptosis in endothelial cells in preclinical models.…”
Section: Tubulin Destabilizersmentioning
confidence: 99%